2008
DOI: 10.1002/path.2410
|View full text |Cite
|
Sign up to set email alerts
|

MYC translocation‐negative classical Burkitt lymphoma cases: an alternative pathogenetic mechanism involving miRNA deregulation

Abstract: The molecular feature of Burkitt lymphoma (BL) is the translocation that places c-Myc under the control of immunoglobulin gene regulatory elements. However, there is accumulating evidence that some cases may lack an identifiable MYC translocation. In addition, during the EUROFISH project, aiming at the standardization of FISH procedures in lymphoma diagnosis, we found that five cases out of 35 classic endemic BLs were negative for MYC translocations by using a split-signal as well as a dual-fusion probe. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(131 citation statements)
references
References 20 publications
5
124
1
1
Order By: Relevance
“…14 In addition, rare cases that are otherwise characteristic of Burkitt lymphoma but lack MYC-IG rearrangement are acceptable for Burkitt lymphoma as these cases bear a Burkitt-like molecular signature, 13,14 and may upregulate MYC expression by alternative mechanisms possibly involving the modulation of microRNA. 22 Although the new diagnostic criteria are clearly outlined, the practical application is not always straightforward. For example, cases with features slightly deviating from the typical medium-sized monomorphous cytomorphology may be acceptable for Burkitt lymphoma, 14 whereas cases with greater cytomorphological variations would be classified as unclassifiable or diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, rare cases that are otherwise characteristic of Burkitt lymphoma but lack MYC-IG rearrangement are acceptable for Burkitt lymphoma as these cases bear a Burkitt-like molecular signature, 13,14 and may upregulate MYC expression by alternative mechanisms possibly involving the modulation of microRNA. 22 Although the new diagnostic criteria are clearly outlined, the practical application is not always straightforward. For example, cases with features slightly deviating from the typical medium-sized monomorphous cytomorphology may be acceptable for Burkitt lymphoma, 14 whereas cases with greater cytomorphological variations would be classified as unclassifiable or diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that classic Burkitt morphological features with a very high proliferation fraction should still be considered as a BL, even when there is a negative MYC translocation. 24 This group has found an alternative mechanism of c-MYC upregulation in these rare negative cases not identified by the commercial FISH probes. 24 Moreover, studies have shown that those cases morphologically diagnosed BL, with a very high proliferation index and negative c-MYC, who were treated with less aggressive chemotherapy for a DLBCL, tended to have worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…An example is c-MYC, which seems to be regulated mainly by miR-34b/c. 53,54,46 This can presumably be explained by the enhanced complementarity between the miR-34b seed sequence and the seed-matching sequence in the c-MYC 3 0 -UTR, when compared with miR-34a (Table 1; Figure 2b). The induction of miR-34 genes allows p53 to regulate the expression of a large number of proteins, even after their transcripts have already been synthesized.…”
Section: Btg4mentioning
confidence: 99%